Efektivitas Penerapan Modul Pembelajaran Instalasi Motor Listrik - Bahta Putri wulandari; Elfizon Elfizon (Jurnal Pendidikan Teknik Elektro, 2023)
This study aims to determine the effectiveness of the electric motor installation learning module on student learning outcomes in the electric motor installation subject in class XI TITL SMKN 5 Padang. The value of student learning outcomes in knowledge competence is still low with an average student under SKM. The cause of the low scores of students is that they still apply the teacher-centered learning technique by the teacher. As a result, student experience difficulties in understanding the material. This study used a quantitative approach with a pre-experimental type using a one-class posttest design. The object of this research is the learning module and the effectiveness of learning outcomes that will occur in the subject of electric motor installation. The subjects in this study were students of class XI TITL SMKN 5 Padang. The research instrument used was in the form of post-test questions in an objective form. Research gives the effect of post-test scores after applying the module as a learning medium is good. Based on the classical completeness test and the effect size test, it is effective. It can be concluded that the application of media modules in learning electric motor installation is said to be effective because the classical values and effect sizes are included in the high category.